Literature study of people's views on the use of mosques as a place for Democratic Parties - Hafsyah, Ade Safitri (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2024)
Abstract Mosques have become important centers in social, religious, and political life in various contexts, including the United States, Europe, and Indonesia. This paper aims to explore the public's views on the use of mosques as a place for democratic parties and their implications in social and political contexts. This research method involves an in-depth literature study of various academic sources, including scientific journals, books, and research reports. Findings from literature studies show that in the United States, literature studies show a positive relationship between mosque attendance and political engagement, with mosques serving as community centers that facilitate political discussion and participation. In Europe, trends show a link between mosque attendance and political participation, highlighting the role of religion in strengthening community engagement. In Indonesia, the historical and cultural context of mosques affects people's views on the use of mosques for political activities. Some people see it as a legitimate form of political activism, while others see it as a violation of the mosque's primary purpose as a place of worship. The social and political implications of using mosques for democratic activities include their impact on social dynamics, election results, and democratic legitimacy. The importance of understanding the diverse views of society and the implications of using mosques for political activities is to formulate inclusive and sustainable policies and strengthen the foundations of democracy in Indonesia. Keywords: democracy, political participation, politics